MANAJEMEN TATA RUANG PERPUSTAKAAN INSTITUT AGAMA ISLAM NEGERI (IAIN) PONTIANAK - Permana, Wike Fitrah; Madeten, Sisilya Saman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe studi is about Spatial Management of the library Islamic Institute natiowide (IAIN) Pontianak. The purpose of this research is to know how the spatial management of the library IAIN Pontianak and the obstacle facing the library in the spatial planning. The method used is descpritive and qualitative approach that provides a profile based on data. Obtained data collection is done in observasi, interview and documentation. Research show that the spatial library IAIN Pontianak at present is not quites as good, this can be seen from the spatial of the collection room on the second floor the collection room reference and descryption on the third floor. The placement of the tools and facilities and furniture of the availabel library is not fully assembled and decorated properly in addition. The lighting and the weather of the collection refrence halls felt uncomfortable. Some problems have come up as obstacels to the superintendent to condition the room, seeing before it that the rooms on the second and third floors are arranged according to user needs. In the sheltering of leader and the administrator the party continues to work out the issues in the library generous budget.Keywords: Library University, Management, Spatial